2022
DOI: 10.1038/s41598-022-14522-1
|View full text |Cite
|
Sign up to set email alerts
|

Utility of targeted next generation sequencing for inborn errors of immunity at a tertiary care centre in North India

Abstract: Inborn errors of immunity (IEI) are a heterogeneous group of monogenic disorders that include primary immunodeficiency’s and other disorders affecting different aspects of the immune system. Next-Generation Sequencing (NGS) is an essential tool to diagnose IEI. We report our 3-year experience in setting up facilities for NGS for diagnosis of IEI in Chandigarh, North India. We used a targeted, customized gene panel of 44 genes known to result in IEI. Variant analysis was done using Ion Reporter software. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Diagnostic yield varies among reports, which is due to the difference in the characteristics of study populations and the methods used ( Supplementary Table S3 ). Previous studies used targeted panel sequencing ( 20 , 21 ), CES ( 22 ), whole exome sequencing (WES) ( 23 , 24 ), or whole genome sequencing ( 25 ), and each method has its pros and cons. With targeted gene panel sequencing, in-depth sequencing of selected genes related to IEI is possible, which enables detection of low-level mosaic variants, whereas with methods that can test a large number of genes, diagnostic yield would be increased.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic yield varies among reports, which is due to the difference in the characteristics of study populations and the methods used ( Supplementary Table S3 ). Previous studies used targeted panel sequencing ( 20 , 21 ), CES ( 22 ), whole exome sequencing (WES) ( 23 , 24 ), or whole genome sequencing ( 25 ), and each method has its pros and cons. With targeted gene panel sequencing, in-depth sequencing of selected genes related to IEI is possible, which enables detection of low-level mosaic variants, whereas with methods that can test a large number of genes, diagnostic yield would be increased.…”
Section: Discussionmentioning
confidence: 99%
“…The MENA cohort's higher rate of reported consanguinity, broader clinical spectrum and more systematic application of WES likely contributed to their overall higher diagnostic yield. However, our approach produced at least comparable yields to TGP-focused or mixed sequencing approaches applied to IEI-specific diagnostics in other resource-constrained settings [13,[141][142]. Some studies reported a smaller incremental gain in diagnostic yield from the addition of WES to TGPs [4,141], but ours was significantly higher.…”
Section: Many Of Our Index Patients Did Not Present With the Most 'Ca...mentioning
confidence: 69%
“…Thus, in many settings, TGPs still remain the preferred first-line approach for IEIrelated molecular diagnostic testing and are particularly useful for specific clinical presentations associated with a limited and stable repertoire of monogenic etiologies, or where somatic mosaicism or recurrent mutations may be involved. Diagnostic yields reported for IEI-focused TGPs in selected cohorts are comparable to those reported for WES and rarely higher than 40%, unless enriched for consanguinity or select clinical phenotypes [11][12][13].…”
Section: Introductionmentioning
confidence: 65%
“…Yet, genetic tests are still not widely available and affordable to be routinely used in clinical diagnosis and screening, particularly in developing countries. 11 Whole-exome sequencing has emerged as an effective tool for the identification of the underlying genetic causes of rare disorders, such as IEIs. 8 By capturing and analyzing the protein-coding regions of the genome, WES provides valuable insights into the causative gene variants, offering the potential for a more accurate and timely diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to gathering medical and family histories, conducting a physical examination, and a thorough assessment of the immune system function by testing blood or administering vaccines, genetic testing is often necessary to accurately diagnose a patient. Yet, genetic tests are still not widely available and affordable to be routinely used in clinical diagnosis and screening, particularly in developing countries 11 …”
Section: Introductionmentioning
confidence: 99%